The Effect of The Role Playing Learning Model on The Science Learning Outcomes of Grade V Students - Simbolon, Mangatur Gonzales; Sirait, Esti Marlina; Siahaan, Theresia Monika (Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to determine the effect of the Role Playing learning model on the IPAS learning outcomes of fifth-grade students at UPTD SD Negeri 124394 Permatangsiantar. The background of this study is the low IPAS learning outcomes of students due to a lack of interest, low participation, and a learning model that is still conventional. The Role Playing model was chosen because it encourages students to be brave in front of others, improves their mastery of the material, and boosts their confidence. The type of research used was quantitative research with a One Group Pretest-Posttest experimental design, with a sample size of 22 students. The data collection techniques used were tests and documentation. The data analysis techniques used were Normality and Hypothesis tests. Based on the results of data analysis, it can be seen that there was an increase in the average score of students' IPAS learning outcomes from 52,5 to 83,1. The hypothesis results obtained were sig. 2-tailed = 0.00 < 0.05 and tcount = 17.259 > ttable 1.721, so H0 is rejected and Ha is accepted, indicating that there is an effect of the Role Playing learning model on the IPAS learning outcomes of fifth-grade students at UPTD SD Negeri 124394 Pematangsiantar